Impact of Guided Discovery Learning and Problem-Based Learning on Students’ Achievement and Locus of Control - Lazuardi Nugroho; Mathilda Susanti; Fariz Budi Arafat (Universitas Sarjanawiyata Tamansiswa, 2026)
Learning achievement is influenced by learning models and students’ locus of control. However, empirical evidence on the interaction between Guided Discovery Learning and Problem-Based Learning with locus of control is still limited, creating an urgent need for this study. Therefore, this research aims to investigate the effects of Guided Discovery Learning and Problem-Based Learning on students’ mathematics achievement by considering locus of control as a blocking variable. Using a quasi-experimental Randomized Complete Block Design, two groups of 32 seventh-grade students were assigned to GDL and PBL. Data from pretest–posttest instruments and an LoC questionnaire were analyzed using descriptive statistics and Two-Way ANOVA. Results showed that the learning model significantly affected achievement, while its interaction with LoC wasn’t significant, although I-LoC students performed better on average. These findings indicate that structured, supportive models like GDL and PBL can reduce LoC-related differences and emphasize the need for future mathematics instruction that promotes guided exploration and equitable learning environments.